ClpB: a chaperone for protein disaggregation - Zolkiewski, Michal (Henry Stewart Talks, 2007)
ClpB, a AAA+ ATPase capable of reactivating aggregated proteins, ATP-dependent translocation of aggregated substrates through a channel in the oligomeric ClpB, Role of the N-terminal domain of ClpB in substrate binding, Role of the DnaK system of co-chaperones in the ClpB-mediated aggregate reactivation, Mechanisms of substrate recognition by ClpB
Archived at 2020/08/13